Sosialisasi Protokol Kesehatan Covid 19 bagi Anak Usia Sekolah di Desa Eonbesi, Kecamatan Mollo Utara, Kabupaten Timor Tengah Selatan - Maria Paulin Saridewi; Yunawati Sele (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2023)
By knowing the dangers of the impact of Covid 19 for humans, especially for people with a history of asthma, heart disease, diabetes, liver including for the elderly and school-age children, it is necessary to conduct socialization for school-age children about the Covid 19 health protocol. This service activity was preceded by by conducting preliminary observations on population data, especially the number of school-age children in the Eonbesi Village area, North Mollo District. The next step is for the service team to prepare the tools and materials needed to carry out socialization activities for the Covid-19 health protocol, including water and hand sanitizers which are used to socialize school-age children in Eonbesi Village about how to wash hands properly and correctly. Next is to give masks to school-age children and teach them how to use masks properly and correctly. The results of this community service show that early childhood in Eonbesi Village understand and understand how the health protocol against Covid 19. The conclusion of the implementation of this community service activity is that the community, especially parents, really welcome this activity considering that Covid 19 is still in the world and with socialization This health protocol helps children become more aware of the dangers of Covid 19 that still lurks.